Synergistic effects of GSK3 and p38 MAPK inhibitors on growth of Plasmodium falciparum ex vivo - Marhalim, L.; Embi, N.; Sidek, H.M. (Penerbit Universiti Kebangsaan Malaysia, 2014)
Pharmacological inhibitors of glycogen synthase kinase 3 (GSK3) and p38 mitogen-activated protein kinase (p38 MAPK), two kinases commonly associated with signaling within cells, have been shown to suppress in vivo or ex vivo growth of plasmodial sp. Here we evaluated antiplasmodial activities ex vivo of four inhibitors against GSK3 [lithium chloride (LiCl),kenpaullone, (2’Z, 3’E)-6-bromoindirubin-3’-oxime (BIO) and SB216763]; and two against p38 MAPK (RWJ67657 and SB202190) individually and in combination preparatory to understanding the role of protein kinases in plasmodial development.The order of decreasing growth-suppressing potencies of the GSK3 inhibitors tested against Plasmodium falciparum 3D7 cultured ex vivo in erythrocytes was BIO (IC50=3.13 μM) > kenpaullone (IC50 = 18.3 μM) > SB216763 (IC50= 27.12 μM)> LiCl (IC50= 25 468 μM). The p38 MAPK inhibitor, RWJ67657, displayed an IC50 of 7.52 μM against 3D7. SB202190 was less effective at inhibiting 3D7 displaying an IC50 of 14.80 μM. When tested in combination, marked synergism was observed for combination of BIO or SB216763 with RWJ67657. In conclusion, GSK3 and MAPK inhibitors showed potent antiplasmodial activities. Synergistic effects observed between BIO or SB216763 and RWJ67657 in inhibiting plasmodial growth may implicate interaction between MAPK and GSK3 pathways and warrant further investigation.